2016
DOI: 10.1149/2.0151609jes
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis and Very Stable Cycling of Polyvinylidene Dichloride Derived Carbon: Sulfur Composite Cathode

Abstract: Activated microporous carbon with narrow pores up to 1 nm, high surface area of about 1000 m 2 /g and pore volume of 0.43 cc/g was synthesized by facile one-step carbonization of polyvinylidene dichloride (PVDC) resin at high temperature without any additional activation process and was used for the preparation of sulfur-carbon (S/C) composite electrodes with sulfur content of 40 wt% in the composite S/C powder and 32 wt% in the composite electrode. The electrodes thus obtained, demonstrate a very stable cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
38
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 51 publications
5
38
1
Order By: Relevance
“…To explain the absence of this discharge voltage plateau, the authors proposed a hypothesis that the Gibbs free energy of the reaction between sulfur and lithium ions could change because sulfur in the micropores could be mixed with carbon at the atomic level rather than as a form of sulfur (S 8 ). Similar discharge behavior of sulfur-microporous composite electrodes in organic liquid electrolyte [36][37][38][39][40] has been reported by other workers with excellent cell cycling durability demonstrated.…”
Section: Sulfur-porous Carbonaceous Nanocompositessupporting
confidence: 86%
See 1 more Smart Citation
“…To explain the absence of this discharge voltage plateau, the authors proposed a hypothesis that the Gibbs free energy of the reaction between sulfur and lithium ions could change because sulfur in the micropores could be mixed with carbon at the atomic level rather than as a form of sulfur (S 8 ). Similar discharge behavior of sulfur-microporous composite electrodes in organic liquid electrolyte [36][37][38][39][40] has been reported by other workers with excellent cell cycling durability demonstrated.…”
Section: Sulfur-porous Carbonaceous Nanocompositessupporting
confidence: 86%
“…Since the use of CMK-3 [6] and other mesoporous carbons [28][29][30][31] made a significant advance in improving specific capacity and durability of the sulfur electrode, researchers' attention has moved to carbons with different pore-sizes (e. g. microporous [32][33][34][35][36][37][38][39][40] and macroporous carbon [41,42] ). In 2010, Zhang et al demonstrated a specific capacity of~890 mAh/gS at 200 mA/gS using a sulfur-microporous carbon composite with a narrow pore size distribution of carbon (~0.7 nm).…”
Section: Sulfur-porous Carbonaceous Nanocompositesmentioning
confidence: 99%
“…This type of behavior schematically presented in Fig. 1b is generally observed for organic carbonatebased electrolyte solutions, [13][14][15][16][17][18][19][20][21][22]24,25,27,31,33,35,36,39,40 as well as for bis(fluorosulfonyl)imide (FSI) anion-based ionic liquid electrolyte solutions. 28,37,38 For this type of the operation of Li-S cells voltage profiles differ from those commonly measured for conventioanal Li-S composite electrodes and are characterized by a single galvanostatic charge/discharge voltage plateau observed around 2.0 V vs. Li/Li + .…”
mentioning
confidence: 72%
“…18,[42][43][44] In the case of liquid electrolytes Wang et al proposed that this type of unique behavior (namely, the single plateau observation) relates to the reaction of Li ions after desolvation with sulfur encapsulated in the micropores under solvent deficient conditions and called this mechanism "quasi-solid-state reaction". 15,45 In most cases this mechanism is observed for composite S/C electrodes with very narrow micropores which width is lower than 1 nm, [14][15][16]19,20,22,23,28,40 but in some cases this type of operation was described also for larger pore size. 13,29,[37][38][39] Several explanations for this single-plateau behavior can be found in the literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation